Eicosapentaenoic Acid Alleviates Inflammatory Response and Insulin Resistance in Pregnant Mice With Gestational Diabetes Mellitus - Yuan, J; Wang, Y; Gao, J; Zhang, X; Xing, J (Physiological research, 2024)
This study investigated the effect of eicosapentaenoic acid (EPA) on insulin resistance in pregnant mice with gestational diabetes mellitus (GDM) and underlying mechanism. C57BL/6 mice fed with a high-fat diet for 4 weeks and the newly gestated were selected and injected with streptozotocin for GDM modeling. We demonstrated that the fasting insulin levels (FINS) and insulin sensitivity index (ISI) in serum and blood glucose level were significantly higher in GDM group than in normal control (NC) group. The low or high dose of EPA intervention reduced these levels, and the effect of high dose intervention was more significant. The area under the curve in GDM group was higher than that of NC group, and then gradually decreased after low or high dose of EPA treatment. The serum levels of TC, TG and LDL were increased in GDM group, while decreased in EPA group. GDM induced down-regulation of HDL level, and the low or high dose of EPA gradually increased this level. The levels of p-AKT2Ser, p-IRS-1Tyr, GLUT4, and ratios of pIRS-1Tyr/IRS-1 and pAKT2Ser/AKT2 in gastrocnemius muscle were reduced in GDM group, while low or high dose of EPA progressively increased these alterations. GDM enhanced TLR4, NF-kappaB p65, IL-1beta, IL-6 and TNF-alpha levels in placental tissues, and these expressions were declined at different dose of EPA, and the decrease was greater at high dose. We concluded that EPA receded the release of inflammatory factors in the placental tissues by inhibiting the activation of TLR4 signaling, thereby alleviating the IR.
Keywords: Animals; gestační diabetes; Female; Diabetes, Gestational; ženské pohlaví; toll-like receptor 4; kyselina eikosapentaenová; Placenta; lidé; Blood Glucose; Mice; těhotenství; Eicosapentaenoic Acid; Insulin; myši; Toll-Like Receptor 4; Insulin Resistance; inzulinová rezistence; zvířata; Pregnancy; Mice, Inbred C57BL; placenta; inzulin; krevní glukóza; myši inbrední C57BL; Humans